The role of customer orientation in improving services in public administration = Rola orientacji na klienta w doskonaleniu usług w administracji publicznej - Ludwiczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The article presents the problem of improvement in public administration offices in one of the most important current principles of quality management - customer orientation in the context of the of BS EN ISO 9001:2009. The results of the author's research in the use of this orientation in selected government offices are presented. The article explores the deficiencies that occur in the offices surveyed in this respect and presents examples of possible methods and tools for the study of the needs, requirements and expectations of customers and techniques for the measurement of their satisfaction that may be used in public administration.
Keywords: orientacja na klienta; administracja publiczna; zarządzanie jakością; customer orientation; public administration; quality management system